Comparison of three behavior modification techniques for management of anxious children aged 4–8 years - Radhakrishna, Sreeraksha (J Dent Anesth Pain Med, 2019)
BACKGROUND: An inability to cope with threatening dental stimuli, i.e., sight, sound, and sensation of airotor, manifests as anxiety and behavioral management problems. Behavior modification techniques involving pre-exposure to dental equipment will give children a first-hand experience of their use, sounds, and clinical effects. The aim of this study was to compare the techniques of Tell-Show-Play-doh, a smartphone dentist game, and a conventional Tell-Show-Do method in the behavior modification of anxious children in the dental operatory. METHODS: Sixty children in the age group of 4-8 years, with Frankl's behavior rating score of 2 or 3, requiring Class I and II cavity restorations were divided into three groups. The groups were Group 1: Tell-Show-Play-doh; Group 2: smartphone dentist game; and Group 3: Tell-Show-Do technique and each group comprised of 20 children. Pulse rate, Facial Image Scale (FIS), Frankl's behavior rating scale, and FLACC (Face, Leg, Activity, Cry, Consolability) behavior scales were used to quantify anxious behavior. Operator compliance was recorded through a validated questionnaire. RESULTS: The results showed lower mean pulse rates, lower FIS and FLACC scores, higher percentage of children with Frankl's behavior rating score of 4, and better operator compliance in both the Tell-Show-Play-doh and smartphone dentist game groups than in the conventional Tell-Show-Do group. CONCLUSION: The Tell-Show-Play-doh and smartphone dentist game techniques are effective tools to reduce dental anxiety in pediatric patients.